ASIAN CHRISTOLOGY: SOME STRAY REFLECTIONS - Athappilly, Sebastian (Asian Horizons, 2017)
In the New Testament as well as in the tradition of the church we do not find one single Christology, but various Christologies. Depending on the concrete contexts and the addressees the various Christologies are, however, united based on the faith in Jesus as the Christ, the Son of God and the only Mediator between God and the humans. Asia being a vast continent of plurality of cultures, religions and existential problems, will and should have similarly a plurality of Christologies, which are Asian and at the same time Christian (based on the biblical faith and the tradition of the church). Inculturation is a valid concern of Asian Christologies, which should be pursued at the same time with sensitivity to the faith of the Christian community and also with due respect for the faith of the adherents of other religions. Already the Christologies of the New Testament are Asian Christologies. In the Indian religious, cultural and socio-political context we have to develop also other forms of an Asian Christology addressing especially the search of the people for justice, harmony and integral salvation. In this perspective we have to give due considerations to the patrimony of each individual church on the one hand and to the aspirations of the local contexts, especially of the tribals, women, Dalits and the subaltern cultures. Christology is not to be seen as limited to academic works and exercise, but is to be seen extended to every form and praxis of Christian spirituality and service and to the expression and appreciation of Christian faith in art, music and literature.